A method for preparing substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties

Single-wall carbon nanotube sol was prepared by arc discharge method, and a substrate-free cloth sandwich structure was formed by gas filtration adsorption molding method, which solved the problem that single-wall carbon nanotube films needed for substrate materials, and achieved high conductivity and excellent Electromagnetic shielding performance.

CN116239105BActive Publication Date: 2025-02-18JIANGXI COPPER TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310251172.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2025-02-18
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

In the prior art, single-wall carbon nanotube films need to be deposited on the substrate material, which limits its application and has defects in strength, flexibility and prevention of shedding, making it difficult to meet the needs of wearable and electromagnetic shielding materials.

Method used

Single-wall carbon nanotube sol is prepared by arc discharge method, and it is self-assembled and deposited by gas filtration adsorption molding to form a cloth-shaped sandwich structure without a substrate, achieving high conductivity and excellent electromagnetic shielding performance.

Benefits of technology

The baseless single-wall carbon nanotube cloth prepared has high conductivity, lightweight and high strength, excellent electromagnetic shielding performance and good flexibility. It can achieve -55dB electromagnetic shielding effect in the frequency range of 8.2 to 12.4GHz without the need for The base material avoids the problem of shedding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116239105B_ABST
    Figure CN116239105B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties. The preparation method firstly adopts an arc discharge method to prepare a single-walled carbon nanotube sol, and then the single-walled carbon nanotube sol is subjected to a gas filtration adsorption molding method to achieve self-assembly deposition of the single-walled carbon nanotube sol to form a cloth-like sandwich structure product, and finally prepares a substrate-free single-walled carbon nanotube cloth with high conductivity and electromagnetic shielding properties. Raman characterization of the single-walled carbon nanotube cloth G / I D The density is 60 or above and 0.05 to 0.1 g / cm 3 , the maximum tensile strength is 7.4MPa, the conductivity is 0.2~5.0S / cm, and it has the characteristics of light weight, high strength and good conductivity. At the same time, the single-walled carbon nanotube cloth does not need to be processed later, and can be directly cut according to size. It has excellent electromagnetic shielding performance. The electromagnetic shielding value in the frequency range of 8.2~12.4GHz is always maintained at around ‑55dB, which has important commercial and military application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation, and in particular relates to a method for preparing a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties. Background Art

[0002] Carbon nanotubes (CNTs) are new nanocarbon materials with a large aspect ratio formed by curling graphene sheets. Generally, according to the number of graphene sheets, they can be divided into single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes (DWCNTs) and multi-walled carbon nanotubes (MWCNTs). Compared with multi-walled carbon nanotubes, single-walled carbon nanotubes have more structural characteristics and performance advantages: the diameter distribution range of single-walled carbon nanotubes is smaller, usually 0.4-2nm; at the same time, there are fewer defects, and they have a higher degree of graphitization and crystallinity. Therefore, single-walled carbon nanotubes have many excellent properties such as high light transmittance, high conductivity, and high carrier mobility. In addition, single-walled carbon nanotubes also have higher development potential in terms of material mechanics, mechanical properties, electrochemical properties, electromagnetic shielding, etc. At present, the main methods for preparing single-walled carbon nanotubes in small batches are floating chemical vapor deposition (FCCVD) and arc discharge. After years of accumulation and exploration, we have achieved good results in the preparation of single-walled carbon nanotubes using arc discharge technology, but the market is still in the development stage. It is of great significance to be able to efficiently and massively prepare high-quality, low-cost single-walled carbon nanotubes.

[0003] Electromagnetic shielding materials are usually made by coating, deposition, impregnation, sputtering, weaving and other methods to make the materials attached or worn to the surface of the shielded object, which can reduce the damage of electromagnetic wave radiation to the human body or electronic equipment. Single-walled carbon nanotubes not only have excellent mechanical strength, but also have excellent conductivity. Single-walled carbon nanotube materials with good impedance matching designed with suitable structures will have natural advantages in electromagnetic shielding applications. In the macroscopic structure prepared by single-walled carbon nanotubes, they usually exist in the form of powders, and can also be produced in the form of films. Usually, carbon tube films are formed by assembling carbon tubes by pushing, shearing, pressing and dry pulling when the single-walled carbon nanotubes are prepared at low yield. Single-walled carbon nanotube films can be directly formed into devices for use, and have application prospects in transparent conductive films, sensors, integrated circuits and the like. In the prior art, single-walled carbon nanotube films deposited on flexible substrates prepared by chemical vapor deposition using carbon monoxide as a carbon source have the characteristics of transparent conductivity, but carbon nanotubes need to be deposited on a substrate material. There are also films for electromagnetic shielding that add amorphous carbon as a buffer layer structure in carbon nanotubes. Although it has a good shielding effect, the material size is not easy to control and enlarge. Chemically cross-linked MXene-coated carbon nanotube composite films are also used. The films after chemical cross-linking treatment have mechanical strength, can be prepared in large sizes, and have excellent electromagnetic shielding performance. And the carbon nanotube dispersion is deposited on the modified non-woven fabric after multiple impregnation and drying to form a macroscopic carbon tube cloth. Due to the yield limit of single-walled carbon nanotubes, the single-walled carbon nanotube films prepared by these methods usually need to be deposited on substrate materials such as PET film, cellulose film, nylon film, etc., which limits its application to a certain extent. At the same time, it also has defects in strength, flexibility and prevention of falling off. This will be greatly limited in the application of electromagnetic shielding materials with customizable sizes and wearable functions. Summary of the invention

[0004] The invention discloses a method for preparing a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties, so as to solve the above and other potential problems of the prior art.

[0005] In order to solve the above problems, the technical solution of the present invention is: a method for preparing a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties, the preparation method first adopts an arc discharge method to prepare a single-walled carbon nanotube sol, and then the single-walled carbon nanotube sol is subjected to a gas filtration adsorption molding method to achieve self-assembly deposition of the single-walled carbon nanotube sol to form a cloth-like sandwich structure product, and finally prepares a substrate-free single-walled carbon nanotube cloth with high conductivity and electromagnetic shielding properties.

[0006] Furthermore, the preparation method specifically comprises the following steps:

[0007] S1) using a catalyst and an additive in an appropriate ratio as an anode and an electrode rod as a cathode to form an arc reaction zone, introducing a carbon source gas and cracking it to prepare a single-walled carbon nanotube sol;

[0008] S2) adjusting the temperature of the discharge port to a set temperature, and allowing the single-walled carbon nanotube aerosol obtained in S1) to follow the carrier gas through the discharge port into the gas filter adsorber under negative pressure, and condense to form a long filamentous product;

[0009] S3) The filamentous product is deposited on the substrate that is in reciprocating motion by adjusting the negative pressure to form a cloth-like sandwich structure product, and finally a substrate-free single-walled carbon nanotube cloth with high electrical conductivity and electromagnetic shielding is obtained.

[0010] Further, the specific steps of S1) are:

[0011] S1.1) The catalyst and the additive are mixed in a certain mass ratio and used as the anode, and the electrode rod is used as the cathode, and the arc reaction zone in the furnace is heated to the cracking temperature under a certain current and voltage;

[0012] S1.2) The carbon source gas is introduced into the arc reaction zone through the carrier gas for high-temperature cracking, and aggregated to form single-walled carbon nanotube aerosol.

[0013] Furthermore, the mass ratio of the additive in S1.1) to the catalyst is 0.1% to 10%;

[0014] The catalyst is pure iron, cast iron, A3 steel, ferrosilicon, ferromanganese, ferrochrome, ferrotungsten, ferromolybdenum, iron oxide or an alloy thereof;

[0015] The auxiliary agent is hydrogen sulfide, elemental sulfur, ferrous sulfide or thiophene;

[0016] The cracking temperature in S1.2) is 1000°C to 3000°C.

[0017] Further, the set temperature in S2) is 80°C to 500°C;

[0018] The negative pressure is a relative pressure of -0.01 MPa to -0.1 MPa.

[0019] Further, the specific process of S3) is:

[0020] S3.1) Start the motor to adjust the substrate to the discharge port, and move it back and forth horizontally and vertically at the discharge port at a moving speed of 0.001 cm / s to 0.5 cm / s;

[0021] S3.2) in a negative pressure state of a relative pressure of -0.05 MPa to -0.1 MPa, the single-walled carbon nanotube filamentous product forms a dense layer on the substrate;

[0022] S3.3) Continue to adjust the negative pressure state to a relative pressure of -0.01MPa to -0.05MPa. The single-walled carbon nanotube filamentous product forms a loose layer in the dense layer, forming a cloth-like sandwich structure product, and finally obtains a substrate-free single-walled carbon nanotube cloth with high conductivity and electromagnetic shielding properties.

[0023] Furthermore, the electrical conductivity of the single-walled carbon nanotube cloth is 0.2-5.0 S / cm, and the electromagnetic shielding within the frequency range of 8.2-12.4 GHz can reach -55 dB.

[0024] Furthermore, the thickness of the single-walled carbon nanotube cloth is 0.01 μm to 1 cm, the size is 0.1 cm*0.1 cm to 2 m*10 m, and the density is 0.05 to 0.1 g / cm 3 , the maximum tensile strength is 7.4MPa.

[0025] Another object of the present invention is to provide a device for implementing the above-mentioned preparation method, wherein the device comprises a carbon nanotube synthesis unit and a gas filtration adsorber unit;

[0026] Wherein, the carbon nanotube synthesis unit is used to prepare single-walled carbon nanotube sol by arc discharge method;

[0027] The gas filtration adsorber unit is used to form a cloth-like sandwich structure product by subjecting the single-walled carbon nanotube aerosol to self-deposition through a gas filtration adsorption molding method.

[0028] Further, the gas filter adsorber unit comprises a housing, a discharge pipe, a substrate, a vacuum pump, a guide rail and a traction motor;

[0029] Wherein, a feed port is provided at one end of the shell, and the other end is connected to the vacuum pump, and the feed port is connected to the discharge port of the carbon nanotube synthesis unit through a discharge pipe;

[0030] The guide rail is arranged inside the shell and is located near the feed port, the traction motor and the base are both movably arranged on the guide rail, and the output end of the traction motor is connected to the bottom of the base;

[0031] The substrate is a ceramic filter disc, filter paper, filter cloth, or stainless steel mesh, and the mesh number is 50-800 meshes.

[0032] The substrate-free single-walled carbon nanocloth of the present invention refers to a carbon nanocloth composed entirely of carbon tubes, which can be independently formed without the need for substrate materials such as PET and fiber membranes; the filamentous single-walled carbon nanotubes described in the present invention are independently deposited on the substrate of the gas filter adsorber, and the single-walled carbon nanotube product is deposited on a ceramic filter sheet, filter paper, filter cloth, stainless steel mesh and other substrates with gaps for filtering gas, and the grown carbon nanotube cloth product can be directly peeled off from such a substrate.

[0033] The single-walled carbon nanotube cloth formed by the present invention has a sandwich structure, with an inner tight layer and an outer loose layer. This sandwich structure plus the dielectric shielding effect of the single-walled carbon nanotubes give it an excellent electromagnetic shielding effect. At the same time, the carbon nanocloth in the present invention has many advantages such as being able to be cut to any size and being wearable, making it more widely used in commercial and militarized electromagnetic shielding.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. High-temperature arc discharge technology can efficiently produce a large number of high-quality single-walled carbon nanotubes. Compared with other preparation technologies, the arc discharge method has higher energy, and the prepared single-walled carbon nanotubes have the advantages of high crystallinity, few defects, high conductivity and high yield;

[0036] 2. Through the control of the temperature gradient inside the furnace, the generated single-walled carbon nanotube aerosol forms a single-walled carbon nanotube filament product at the discharge port, and then the single-walled carbon nanotube is self-assembled and deposited into a cloth-like structure through gas filtration and adsorption molding. This cloth-like product formed on the basis of the filamentary structure can maintain the mechanical strength of the single-walled carbon nanotube to a great extent. The prepared single-walled carbon nanotube cloth has the advantages of light weight and high strength compared with existing products;

[0037] 3. By controlling the negative pressure conditions during the deposition process, a single-walled carbon nanotube cloth with a sandwich structure can be prepared. The middle layer in the sandwich structure is a dense layer with certain toughness and strength deposited under a larger negative pressure condition, and the outer contact layer is a loose layer deposited under a smaller negative pressure condition. This special structure can maintain the stability of the large-scale structure, allowing the single-walled carbon nanotube cloth to be directly taken out after forming without the need for a substrate material, which greatly improves the defects of the existing carbon tube film materials such as substrate shedding during use;

[0038] 4. Single-walled carbon nanotube cloth has good flexibility. During the preparation process, it can be regulated and deposited into products of any size according to the position of the gas filter adsorber. At the same time, the size can also be cut according to the needs of later use, which makes up for the shortcomings of traditional carbon tube membrane materials in terms of customization;

[0039] 5. The single-walled carbon nanotube cloth in the present invention has strong processability and can be used as a wearable material. At the same time, the single-walled carbon nanotube cloth with a sandwich structure has excellent electromagnetic shielding performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The present invention is a flowchart of a method for preparing a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties.

[0041] Figure 2 The present invention is a schematic diagram of the device structure of a method for preparing a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties.

[0042] Figure 3 This is a schematic diagram of a physical photograph of the single-walled carbon nanotube cloth prepared in Example 1 of the present invention.

[0043] Figure 4 This is a schematic diagram of a scanning electron microscope photograph of the single-walled carbon nanotube cloth prepared in Example 1 of the present invention.

[0044] Figure 5 This is a schematic diagram of a partial magnified scanning electron microscope photograph of the single-walled carbon nanotube cloth prepared in Example 1 of the present invention.

[0045] Figure 6 This is a schematic diagram of a transmission electron microscope photograph of the single-walled carbon nanotubes prepared in Example 1 of the present invention.

[0046] Figure 7 This is a Raman spectrum curve of the single-walled carbon nanotube cloth prepared in Example 1 of the present invention.

[0047] Figure 8 This is a tensile performance test curve of the single-walled carbon nanotube cloth prepared in Example 1 of the present invention.

[0048] Fig. 9 This is a test curve of the electromagnetic shielding performance of the single-walled carbon nanotube cloth prepared in Example 1 of the present invention.

[0049] In the figure:

[0050] 1. Carbon nanotube synthesis unit, 2. Cathode electrode rod, 3. Metal anode, 4. Synthesis unit discharge port, 5. Gas filter adsorber unit discharge pipe port, 6. Traction motor, 7. Adsorber base, 8. Guide rail, 9. Gas filter adsorber unit. DETAILED DESCRIPTION

[0051] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0052] The present invention discloses a method for preparing a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties. The preparation method first adopts an arc discharge method to prepare a single-walled carbon nanotube sol, and then the single-walled carbon nanotube sol is subjected to a gas filtration adsorption molding method to achieve self-assembly deposition of the single-walled carbon nanotube sol to form a cloth-like sandwich structure product, and finally prepares a substrate-free single-walled carbon nanotube cloth with high conductivity and electromagnetic shielding properties.

[0053] like Figure 1 As shown, the preparation method specifically comprises the following steps:

[0054] S1) using a catalyst and an additive in an appropriate ratio as an anode and an electrode rod as a cathode to form an arc reaction zone, introducing a carbon source gas and cracking it to prepare a single-walled carbon nanotube sol;

[0055] S2) adjusting the temperature of the discharge port to a set temperature, and allowing the single-walled carbon nanotube aerosol obtained in S1) to follow the carrier gas through the discharge port into the gas filter adsorber under negative pressure, and condense to form a long filamentous product;

[0056] S3) The filamentous product is deposited on the substrate that is in reciprocating motion by adjusting the negative pressure to form a cloth-like sandwich structure product, and finally a single-walled carbon nanotube cloth with high electrical conductivity is obtained.

[0057] The specific steps of S1) are:

[0058] S1.1) The catalyst and the additive are mixed in a certain mass ratio and used as the anode, and the electrode rod is used as the cathode, and the arc reaction zone in the furnace is heated to the cracking temperature under a certain current and voltage;

[0059] The carbon source gas is introduced into the arc reaction zone through the carrier gas for high-temperature cracking, and aggregated to form single-walled carbon nanotube aerosol.

[0060] The mass ratio of the additive in S1.1) to the catalyst is 0.1% to 10%;

[0061] The catalyst is pure iron, cast iron, A3 steel, ferrosilicon, ferromanganese, ferrochrome, ferrotungsten, ferromolybdenum, iron oxide or an alloy thereof;

[0062] The auxiliary agent is hydrogen sulfide, elemental sulfur, ferrous sulfide or thiophene;

[0063] The cracking temperature in S1.2) is 1000°C to 3000°C.

[0064] The set temperature in S2) is 80°C to 500°C;

[0065] The negative pressure is a relative pressure of -0.01 MPa to -0.1 MPa.

[0066] The specific process of S3) is:

[0067] S3.1) Start the motor to adjust the substrate to the discharge port, and move it back and forth horizontally and vertically at the discharge port at a moving speed of 0.001 cm / s to 0.5 cm / s;

[0068] S3.2) in a negative pressure state of relative pressure -0.051 MPa to -0.1 MPa, the single-walled carbon nanotube filamentous product forms a dense layer on the substrate;

[0069] S3.3) Continue to adjust the negative pressure state to a relative pressure of -0.01MPa to -0.05MPa. The single-walled carbon nanotube filamentous product forms a loose layer in the dense layer, forming a cloth-like sandwich structure product, and finally obtains a substrate-free single-walled carbon nanotube cloth with high conductivity and electromagnetic shielding properties.

[0070] The substrate-free single-walled carbon nanotube cloth with electromagnetic shielding has an electrical conductivity of 0.2 to 5.0 S / cm, and the electromagnetic shielding in the frequency range of 8.2 to 12.4 GHz can reach -55 dB.

[0071] The thickness of the substrate-free single-walled carbon nanotube cloth with electromagnetic shielding is 0.01 μm to 1 cm, the size is 0.1 cm*0.1 cm to 2 m*10 m, and the density is 0.05 to 0.1 g / cm 3 , the maximum tensile strength is 7.4MPa.

[0072] like Figure 2 As shown, a device used in a method for preparing a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties according to the present invention is shown, and the device comprises:

[0073] The carbon nanotube synthesis unit 1 is used to grow single-walled carbon nanotubes. A specific temperature is maintained in the furnace, and the generated single-walled carbon nanotubes diffuse in the furnace to form an aerosol form.

[0074] Cathode electrode rod 2, using hollow graphite as cathode electrode rod, used to generate plasma arc and provide energy required for growing carbon tubes;

[0075] The metal anode 3 is composed of a specific metal catalyst and an additive to form an anode unit, which is used to provide the catalyst required for growing carbon nanotubes and to generate a plasma arc together with the cathode;

[0076] The synthesis unit discharge port 4 has a temperature gradient at the discharge port. The appropriate temperature gradient can convert the single-walled carbon nanotube aerosol inside the furnace into a single-walled carbon nanotube filament product at the discharge port.

[0077] The gas filter adsorber outlet 5 is connected to an external vacuum pump to provide negative pressure conditions;

[0078] A traction motor 6, used for traction so that the gas filter adsorber can move in all directions;

[0079] The substrate adsorption sheet 7 uses a special movable substrate to filter the gas and adsorb and deposit the single-walled carbon nanotube filament product to form a single-walled carbon nanotube cloth material;

[0080] The guide rail 8 connects the substrate adsorption sheet and the traction motor to enable the substrate to move;

[0081] The gas filtration adsorber unit 9 is used to prepare a single-walled carbon nanotube cloth product.

[0082] A method for preparing single-walled carbon nanotube cloth using the above device has the following characteristics:

[0083] The thickness and size of the single-walled carbon nanotube cloth can be arbitrarily adjusted, the thickness can be 0.01 μm-1 cm, and the size can be 0.1 cm*0.1 cm-2 m*10 m;

[0084] The single-walled carbon nanotube cloth is lightweight and high-strength, with a density of 0.05-0.1 g / cm3 and a maximum tensile strength of 7.4 MPa;

[0085] The single-walled carbon nanotube cloth has the characteristic of high electrical conductivity, with an electrical conductivity of 0.2-5.0S / cm;

[0086] The single-walled carbon nanotube cloth can be cut into any size according to usage requirements, has excellent electromagnetic shielding performance, and the maximum electromagnetic shielding value in the frequency range of 8.2-12.4 GHz can reach -55 dB.

[0087] The method for preparing the substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties comprises the following steps:

[0088] (1) Putting a catalyst and an additive in an appropriate proportion into a crucible at the bottom of an electric arc furnace as an anode 3, and an electrode rod directly above the anode 3 as a cathode 2. Under a certain current and voltage, a high-energy plasma arc is formed between the two in an arc-starting atmosphere as a heat source for preparing single-walled carbon nanotubes;

[0089] (2) controlling the temperature in the furnace, introducing the carbon source gas along with the carrier gas, and the single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4;

[0090] (3) As the temperature of the single-walled carbon nanotube aerosol in the gas filter adsorber unit 9 decreases, it aggregates to form single-walled carbon nanotube filament products. The filament products follow the carrier gas to the surface of the gas filter adsorber substrate 7. The gas is filtered and discharged through the discharge port 5. The filament products are deposited by themselves to form a cloth-like structure product.

[0091] (4) The thickness of the single-walled carbon nanotubes is controlled by controlling the deposition time. The base 7 of the gas filter adsorber is pulled by the motor 6 to move on the guide rail 8, so that base-free single-walled carbon nanotube cloths with electromagnetic shielding properties of different sizes can be continuously prepared.

[0092] The catalyst and the auxiliary agent in the step (1) are appropriately proportioned, wherein the catalyst is an iron metal or its alloy such as pure iron, cast iron, A3 steel, ferrosilicon, ferromanganese, ferrochrome, ferrotungsten, ferromolybdenum, iron oxide, etc., and the auxiliary agent is a sulfur-containing compound such as hydrogen sulfide, elemental sulfur, ferrous sulfide, thiophene, etc., and the proportion is that the mass ratio of the auxiliary agent to the catalyst is 0.1%-10%.

[0093] The temperature in the furnace in step (2) is the temperature required for further forming aerosol above the furnace after single-walled carbon nanotubes are generated in the arc reaction zone, and the temperature is between 1000°C and 3000°C.

[0094] The temperature reduction in step (3) means that there is a large temperature gradient between the feed port and the interior of the furnace, and the temperature of the discharge port is between 80°C and 500°C. The gas adsorber substrate is a material with a specific mesh size that can filter gas and is conducive to the deposition of carbon tubes, such as ceramic filter plates, filter paper, filter cloth, and stainless steel mesh.

[0095] In the step (4), the motor pulls the base of the gas filter adsorber to move, and the base is aligned with the carbon tube discharge port and can reciprocate in the horizontal and vertical directions, respectively, with a moving rate of 0.001 cm / s-0.5 cm / s.

[0096] Example 1

[0097] According to the ratio of catalytic promoter ferrous sulfide to metal catalyst pure iron, 5% is added to the bottom crucible of the arc discharge furnace as the metal anode 3, and the hollow graphite electrode rod directly above it is the cathode 2. Under the current of 500A and the voltage of 100V, a high-energy plasma arc is formed between the positive and negative electrodes in an argon arc-igniting atmosphere as a heat source for preparing single-walled carbon nanotubes.

[0098] The temperature in the furnace is controlled at 2500°C, and carbon source methane gas is introduced along with carrier gas argon. The single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4. The temperature at the discharge pipe 4 is controlled to be 300°C. The single-walled carbon nanotube aerosol aggregates to form single-walled carbon nanotube filamentary products due to the decrease in temperature. The filamentary products reach the surface of the gas filter adsorber substrate 7 together with the carrier gas, and the gas is filtered and discharged through the pipe port 5. The filamentary products are self-assembled and deposited to form a cloth-like structure product.

[0099] When the discharge pipe 4 is fixed to the position of the gas filter adsorber facing it, the reaction time is 5 minutes, and a single-walled carbon nanotube cloth with a thickness of 100 μm can be obtained. After the negative pressure state is controlled to be a relative pressure of -0.07 MPa to obtain a dense layer in the early stage, the pressure is adjusted to -0.02 MPa to obtain a loose layer. Furthermore, the gas filter adsorber is controlled to perform lateral and longitudinal reciprocating motions respectively through the traction motor 6, and the moving rate is controlled to be 0.01 cm / s. When the reaction time is 2 hours, a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties of 50 cm*50 cm and a thickness of 150 μm can be prepared.

[0100] The obtained single-walled carbon nanotube cloth was characterized. The actual photo of the obtained product is shown in Figure 3 As shown, a whole piece of black cloth-like product with a size of approximately 50cm*50cm can be completely taken out. The product is soft in texture and has wrinkles when the surface is uneven. The scanning electron microscope photos of the product are as follows Figure 4 and Figure 5 As shown, at lower magnification, Figure 3 It can be clearly found that the macroscopic cloth-like product is composed of many microscopic filamentous single-walled carbon nanotube films. The size of the microscopic carbon tube film ranges from tens of micrometers to hundreds of micrometers, indicating that there are also obvious wrinkles. Focusing on the surface of the carbon tube film and continuing to magnify the scanning electron microscope, Figure 5 In the transmission electron micrograph, we can clearly see the smooth, curled single-walled carbon nanotube bundles with a length of several microns. The bundles are very dense and arranged layer by layer. Figure 6 As shown in the figure, after the dispersion treatment, the bundled carbon tubes are in a state of aggregation of a few strands, with a length of several hundred nanometers, and the carbon tubes are very straight. Carefully identifying a single carbon tube is a single-walled carbon nanotube. Figure 7 As shown, the detection is performed when the laser wavelength is 532nm. -1 -200cm -1 The characteristic peak of single-walled carbon nanotubes, the RBM peak, appeared nearby. At the same time, there were obvious G peaks and D peaks, two characteristic peaks of carbon materials. The calculation showed that I G / I Dis 75, indicating that the product has a high degree of graphitization and crystallinity. The tensile curve of the product is as follows Figure 8 As shown in the figure, the single-walled carbon nanotube cloth sample was prepared into a standard size of 14 micron thick strips, and the stress-strain curve was tensile tested. It can be seen that when the strain is about 20%, the maximum breaking strength is 7.4MPa, which shows that the material has a high strength. The electromagnetic shielding test curve of the product is shown in Fig. 9 As shown, the single-walled carbon nanotube cloth product can be directly cut into the size required for the test, and the electromagnetic shielding performance test is carried out using the waveguide method. In the frequency range of 8-12.4GHz, the shielding effectiveness can be maintained near -55dB, and has good electromagnetic shielding performance.

[0101] Example 2

[0102] According to the ratio of 10% of the catalytic promoter elemental sulfur to the metal catalyst pure iron, it is added to the bottom crucible of the arc discharge furnace as the metal anode 3, and the hollow graphite electrode rod directly above it is the cathode 2. Under the current of 400A and the voltage of 50V, a high-energy plasma arc is formed between the positive and negative electrodes in an argon arc-igniting atmosphere as a heat source for preparing single-walled carbon nanotubes.

[0103] The temperature in the furnace is controlled at 2500°C, and carbon source methane gas is introduced along with carrier gas argon. The single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4. The temperature at the discharge pipe 4 is controlled to be 300°C. The single-walled carbon nanotube aerosol aggregates to form single-walled carbon nanotube filamentary products due to the decrease in temperature. The filamentary products reach the surface of the gas filter adsorber substrate 7 together with the carrier gas, and the gas is filtered and discharged through the pipe port 5. The filamentary products are self-assembled and deposited to form a cloth-like structure product.

[0104] When the discharge pipe 4 is fixed to the position of the gas filter adsorber facing it, the reaction time is 5 minutes, and a single-walled carbon nanotube cloth with a thickness of 60 μm can be obtained. After the negative pressure state is controlled to be a relative pressure of -0.07 MPa to obtain a dense layer in the early stage, the pressure is adjusted to -0.02 MPa to obtain a loose layer. Furthermore, the gas filter adsorber is controlled to perform lateral and longitudinal reciprocating motions respectively through the traction motor 6, and the moving rate is controlled to be 0.01 cm / s. A single-walled carbon nanotube cloth with a size of 50 cm*50 cm and a thickness of 80 μm can be prepared at a reaction time of 2 hours.

[0105] Example 3

[0106] According to the ratio of catalytic promoter ferrous sulfide to metal catalyst pure iron, 5% is added to the bottom crucible of the arc discharge furnace as the metal anode 3, and the hollow graphite electrode rod directly above it is the cathode 2. Under the current of 500A and the voltage of 100V, a high-energy plasma arc is formed between the positive and negative electrodes in an argon arc-igniting atmosphere as a heat source for preparing single-walled carbon nanotubes.

[0107] The temperature in the furnace is controlled to be 2800°C, and the carbon source methane gas is introduced along with the carrier gas argon. The single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4. The temperature at the discharge pipe 4 is controlled to be 350°C. The single-walled carbon nanotube aerosol is reduced in temperature and aggregates to form single-walled carbon nanotube filament products. The filament products follow the carrier gas to the surface of the gas filter adsorber substrate 7. The gas is filtered and discharged through the pipe port 5. The filament products are self-assembled and deposited to form cloth-like structure products.

[0108] When the discharge pipe 4 is fixed to the position of the gas filter adsorber facing it, the reaction time is 5 minutes, and a single-walled carbon nanotube cloth with a thickness of 120 μm can be obtained. After the negative pressure state is controlled to be a relative pressure of -0.06 MPa to obtain a dense layer in the early stage, the pressure is adjusted to -0.02 MPa to obtain a loose layer. Furthermore, the gas filter adsorber is controlled to perform lateral and longitudinal reciprocating motions respectively by the traction motor 6, and the moving rate is controlled to be 0.01 cm / s. When the reaction time is 2 hours, a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties of 50 cm*50 cm and a thickness of 180 μm can be prepared.

[0109] Example 4

[0110] According to the ratio of catalytic promoter ferrous sulfide to metal catalyst pure iron, 5% is added to the bottom crucible of the arc discharge furnace as the metal anode 3, and the hollow graphite electrode rod directly above it is the cathode 2. Under the current of 500A and the voltage of 100V, a high-energy plasma arc is formed between the positive and negative electrodes in an argon arc-igniting atmosphere as a heat source for preparing single-walled carbon nanotubes.

[0111] The temperature in the furnace is controlled at 2500°C, and carbon source methane gas is introduced along with carrier gas argon. The single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4. The temperature at the discharge pipe 4 is controlled to be 300°C. The single-walled carbon nanotube aerosol aggregates to form single-walled carbon nanotube filamentary products due to the decrease in temperature. The filamentary products reach the surface of the gas filter adsorber substrate 7 together with the carrier gas, and the gas is filtered and discharged through the pipe port 5. The filamentary products are self-assembled and deposited to form a cloth-like structure product.

[0112] When the discharge pipe 4 is fixed to the position of the gas filter adsorber facing it, the reaction time is 20 minutes, and a single-walled carbon nanotube cloth with a thickness of 300 μm can be obtained. After the negative pressure state is controlled to be a relative pressure of -0.07 MPa to obtain a dense layer in the early stage, the pressure is adjusted to -0.02 MPa to obtain a loose layer. Furthermore, the gas filter adsorber is controlled to perform lateral and longitudinal reciprocating motions respectively through the traction motor 6, and the moving rate is controlled to be 0.01 cm / s. When the reaction time is 3 hours, a substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties of 50 cm*50 cm and a thickness of 280 μm can be prepared.

[0113] Example 5

[0114] According to the ratio of catalytic promoter ferrous sulfide to metal catalyst pure iron, 5% is added to the bottom crucible of the arc discharge furnace as the metal anode 3, and the hollow graphite electrode rod directly above it is the cathode 2. Under the current of 500A and the voltage of 100V, a high-energy plasma arc is formed between the positive and negative electrodes in an argon arc-igniting atmosphere as a heat source for preparing single-walled carbon nanotubes.

[0115] The temperature in the furnace is controlled at 2500°C, and carbon source methane gas is introduced along with carrier gas argon. The single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4. The temperature at the discharge pipe 4 is controlled to be 300°C. The single-walled carbon nanotube aerosol aggregates to form single-walled carbon nanotube filamentary products due to the decrease in temperature. The filamentary products reach the surface of the gas filter adsorber substrate 7 together with the carrier gas, and the gas is filtered and discharged through the pipe port 5. The filamentary products are self-assembled and deposited to form a cloth-like structure product.

[0116] When the discharge pipe 4 is fixed to the position of the gas filter adsorber facing it, the reaction time is 60 minutes, and a single-walled carbon nanotube cloth with a thickness of 1 mm can be obtained. After the negative pressure state is controlled to be a relative pressure of -0.07 MPa to obtain a dense layer in the early stage, the pressure is adjusted to -0.02 MPa to obtain a loose layer. Furthermore, the gas filter adsorber is controlled to perform lateral and longitudinal reciprocating motions respectively through the traction motor 6, and the moving rate is controlled to be 0.05 cm / s. A substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties of 200 cm*200 cm and a thickness of 70 μm can be prepared at a reaction time of 4 hours.

[0117] Example 6

[0118] According to the ratio of 15% of the catalytic promoter thiophene to the metal catalyst pure iron, it is added to the bottom crucible of the arc discharge furnace as the metal anode 3, and the hollow graphite electrode rod directly above it is the cathode 2. Under the current of 450A and the voltage of 80V, a high-energy plasma arc is formed between the positive and negative electrodes in an argon arc-igniting atmosphere as a heat source for preparing single-walled carbon nanotubes.

[0119] The temperature in the furnace is controlled to be 2500°C, and the carbon source methane gas is introduced along with the carrier gas argon. The single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4. The temperature at the discharge pipe 4 is controlled to be 300°C. The single-walled carbon nanotube aerosol is reduced in temperature and aggregates to form single-walled carbon nanotube filament products. The filament products follow the carrier gas to the surface of the gas filter adsorber substrate 7. The gas is filtered and discharged through the pipe port 5. The filament products are self-assembled and deposited to form cloth-like structure products.

[0120] When the discharge pipe 4 is fixed to the position of the gas filter adsorber facing it, the reaction time is 30 minutes, and a single-walled carbon nanotube cloth with a thickness of 200 μm can be obtained. After the negative pressure state is controlled to be a relative pressure of -0.07 MPa to obtain a dense layer in the early stage, the pressure is adjusted to -0.02 MPa to obtain a loose layer. Furthermore, the gas filter adsorber is controlled to perform lateral and longitudinal reciprocating motions respectively through the traction motor 6, and the moving rate is controlled to be 0.01 cm / s. A substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties of 200 cm*200 cm and a thickness of 100 μm can be prepared at a reaction time of 6 hours.

[0121] Example 7

[0122] According to the ratio of 15% of the catalyst promoter thiophene to the metal catalyst cast iron, it is added to the bottom crucible of the arc discharge furnace as the metal anode 3, and the hollow graphite electrode rod directly above it is the cathode 2. Under the current of 450A and the voltage of 80V, a high-energy plasma arc is formed between the positive and negative electrodes in an argon arc-igniting atmosphere as a heat source for preparing single-walled carbon nanotubes.

[0123] The temperature in the furnace is controlled at 1500°C, and carbon source methane gas is introduced along with carrier gas argon. The single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4. The temperature at the discharge pipe 4 is controlled to be 200°C. The single-walled carbon nanotube aerosol aggregates to form single-walled carbon nanotube filamentary products due to the decrease in temperature. The filamentary products reach the surface of the gas filter adsorber substrate 7 together with the carrier gas, and the gas is filtered and discharged through the pipe port 5. The filamentary products are self-assembled and deposited to form a cloth-like structure product.

[0124] When the discharge pipe 4 is fixed to the position of the gas filter adsorber facing it, the reaction time is 30 minutes, and a single-walled carbon nanotube cloth with a thickness of 100 μm can be obtained. After the negative pressure state is controlled to be a relative pressure of -0.07 MPa to obtain a dense layer in the early stage, the pressure is adjusted to -0.02 MPa to obtain a loose layer. Furthermore, the gas filter adsorber is controlled to perform lateral and longitudinal reciprocating motions respectively through the traction motor 6, and the moving rate is controlled to be 0.01 cm / s. A substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties of 10 cm*10 cm and a thickness of 100 μm can be prepared at a reaction time of 2 hours.

[0125] Example 8

[0126] According to the ratio of catalytic promoter ferrous sulfide to metal catalyst cast iron of 15%, it is added to the bottom crucible of the arc discharge furnace as the metal anode 3, and the hollow graphite electrode rod directly above it is the cathode 2. Under the current of 450A and the voltage of 80V, a high-energy plasma arc is formed between the positive and negative electrodes in an argon arc-igniting atmosphere as a heat source for preparing single-walled carbon nanotubes.

[0127] The temperature in the furnace is controlled at 2000°C, and carbon source methane gas is introduced along with carrier gas argon. The single-walled carbon nanotube aerosol generated in the carbon nanotube synthesis unit 1 enters the gas filter adsorber unit 9 through the discharge pipe 4. The temperature at the discharge pipe 4 is controlled to be 300°C. The single-walled carbon nanotube aerosol aggregates to form single-walled carbon nanotube filamentary products due to the decrease in temperature. The filamentary products reach the surface of the gas filter adsorber substrate 7 together with the carrier gas, and the gas is filtered and discharged through the pipe port 5. The filamentary products are self-assembled and deposited to form a cloth-like structure product.

[0128] When the discharge pipe 4 is fixed to the position of the gas filter adsorber facing it, the reaction time is 30 minutes, and a single-walled carbon nanotube cloth with a thickness of 150 μm can be obtained. After the negative pressure state is controlled to be a relative pressure of -0.07 MPa to obtain a dense layer in the early stage, the pressure is adjusted to -0.02 MPa to obtain a loose layer. Furthermore, the gas filter adsorber is controlled to perform lateral and longitudinal reciprocating motions respectively through the traction motor 6, while the lateral and longitudinal travel distances are controlled, and the moving rate is controlled to be 0.01 cm / s. A substrate-free single-walled carbon nanotube cloth with electromagnetic shielding properties of 100 cm*10 cm and a thickness of 80 μm can be prepared at a reaction time of 2 hours.

[0129] The single-walled carbon nanotube cloth and its preparation method provided in the embodiments of this application are introduced in detail. The description of the above embodiments is only used to help understand the method and its core idea of ​​this application; at the same time, for ordinary technicians in this field, according to the idea of ​​this application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting this application.

[0130] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problems within a preset error range and basically achieve the technical effects. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be subject to that defined in the attached claims.

[0131] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0132] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0133] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.

Claims

1. A method for preparing a substrate-free single-walled carbon nanotube cloth having electromagnetic shielding properties, characterized in that: The preparation method firstly adopts an arc discharge method to prepare a single-walled carbon nanotube sol, and then the single-walled carbon nanotube sol is subjected to a gas filtration adsorption molding method to achieve self-assembly deposition of the single-walled carbon nanotube sol to form a cloth-like sandwich structure product, and finally prepares a single-walled carbon nanotube cloth without a substrate material with high electrical conductivity and electromagnetic shielding performance. The preparation method specifically comprises the following steps: S1) using a catalyst and an auxiliary agent in an appropriate proportion as an anode and an electrode rod as a cathode to form an arc reaction zone, and introducing a carbon source gas to crack and prepare a single-walled carbon nanotube sol; S2) adjusting the temperature of the discharge port to a set temperature, and allowing the single-walled carbon nanotube aerosol obtained in S1) to follow the carrier gas through the discharge port into the gas filter adsorber under negative pressure, and condense to form a long filamentous product; S3) adjusting the negative pressure to deposit the filamentous product on the substrate that is in reciprocating motion, thereby forming a cloth-like sandwich structure product, and finally obtaining a single-walled carbon nanotube cloth without a substrate material; The specific process is: S3.1) Start the motor to adjust the substrate to the discharge port, and reciprocate horizontally and vertically at the discharge port at a moving speed of 0.001 cm / s to 0.5 cm / s; S3.2) in a negative pressure state of relative pressure -0.051 MPa to -0.1 MPa, the single-walled carbon nanotube filamentous product forms a dense layer on the substrate; S3.3) Continue to adjust the negative pressure state to a relative pressure of -0.01MPa to -0.05MPa, and the single-walled carbon nanotube filamentous product forms a loose layer on the dense layer, forming a cloth-like sandwich structure product, and finally obtains a substrate-free single-walled carbon nanotube cloth with high conductivity and electromagnetic shielding properties; the substrate-free single-walled carbon nanotube cloth refers to a carbon nanotube cloth completely composed of carbon tubes, and the single-walled carbon nanotubes are self-assembled and deposited on a substrate with gaps for filtering gas, and the grown carbon nanotube cloth product can be peeled off from the substrate; The thickness of the single-walled carbon nanotube cloth is 0.01 μm to 1 cm, the size is 0.1 cm*0.1 cm to 2 m*10 m, and the density is 0.05 to 0.1 g / cm 3 The maximum tensile strength is 7.4MPa; the electrical conductivity is 0.2~5.0S / cm, and the electromagnetic shielding in the frequency range of 8.2~12.4GHz can reach -55dB.

2. The preparation method according to claim 1, characterized in that: The specific steps of S1) are: S1.1) the catalyst and the auxiliary agent are mixed in a certain mass ratio as a metal anode, the electrode rod is used as a cathode, and the arc reaction zone in the furnace is heated to the cracking temperature under a certain current and voltage; S1.2) The carbon source gas is introduced into the arc reaction zone through the carrier gas for high-temperature cracking, and aggregated to form single-walled carbon nanotube aerosol.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the auxiliary agent in S1.1) to the catalyst is 0.1% to 10%; the catalyst is pure iron, cast iron, A3 steel, ferrosilicon, ferromanganese, ferrochrome, ferrotungsten, ferromolybdenum or iron oxide; the auxiliary agent is hydrogen sulfide, elemental sulfur, ferrous sulfide or thiophene; the cracking temperature in S1.2) is 1000°C to 3000°C.

4. The preparation method according to claim 1, characterized in that: The set temperature in S2) is 80°C to 500°C.

5. A device for implementing the preparation method according to any one of claims 1 to 4, characterized in that: The device comprises a carbon nanotube synthesis unit and a gas filter adsorber unit, wherein the carbon nanotube synthesis unit is used to prepare single-walled carbon nanotube sol by an arc discharge method; the gas filter adsorber unit is used to make the single-walled carbon nanotube aerosol realize self-assembly and deposition through a gas filtration and adsorption molding method to form a cloth-like sandwich structure product; the gas filter adsorber unit comprises a shell, a discharge pipe, a substrate, a vacuum pump, a guide rail and a traction motor; wherein one end of the shell is provided with a feed port, and the other end is connected to the vacuum pump, and the feed port is connected to the discharge port of the carbon nanotube synthesis unit through the discharge pipe; the guide rail is arranged inside the shell and is located near the feed port, the traction motor and the substrate are both movably arranged on the guide rail, and the output end of the traction motor is connected to the bottom of the substrate; the substrate is a ceramic filter, filter paper, filter cloth, or a stainless steel mesh, and the mesh number is 50 to 800.

Citation Information

Patent Citations

  • Gas-phase continuous preparation method of single-walled carbon nanotube film and special device

    CN104261384A